Manufacturing process of quartz stone plate with good permeability

Through the pickling, ball milling and anti-oxidation modification processes, the problems of poor quality of artificial quartz sand and easy yellowing of resin are solved, and the production of quartz stone slabs with high permeability, anti-permeability and durability are achieved. .

CN119458939APending Publication Date: 2025-02-18GUANGDONG OVERLAND CERAMICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411594330.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The quartz sand quality of existing artificial quartz stone slabs is poor, which affects the quality of the board, and the resin composition is prone to yellowing, resulting in poor durability.

Method used

The impurities in quartz sand are removed by pickling treatment, ball grinding and shaping improves the particle density, anti-oxidation modified unsaturated polyester resin prevents yellowing, and controls the stability of the resin components during the curing process.

Benefits of technology

It improves the permeability, permeability and durability of quartz stone sheets, ensuring high quality and stable performance of the sheets.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a manufacturing process of a quartz stone plate with good permeability. The manufacturing process comprises the following steps: S1, carrying out acid pickling treatment on quartz sand; s2, sequentially washing the pickled quartz sand, adding an alkaline cleaning agent for neutralizing, and cleaning to obtain quartz sand without impurities and residual pickling solution; s3, after drying treatment, carrying out ball-milling molding to obtain quartz sand particles; s4, performing antioxidant modification treatment on unsaturated polyester resin to obtain modified unsaturated polyester resin; s5, obtaining a mixture; s6, the mixed material is unloaded into a preset mold frame, the material is spread to be flat and covered with paper, compression molding is conducted, then curing treatment is conducted, and a plate material is obtained; and S7, the plate is polished, and the quartz stone plate is obtained. The quartz stone plate with good permeability resistance and permeability can be prepared, the unsaturated polyester resin is subjected to antioxidant modification to avoid yellowing of resin components, the permeability of the quartz stone plate during application is kept, and the use durability of the quartz stone plate is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plate production, and in particular to a production process of a quartz stone plate with good permeability. Background Art

[0002] In the field of architectural decoration, stone has become one of the main decorative materials due to its beautiful, elegant and decorative features. Natural marble has been widely used for its rich and natural patterns and natural decorative effects and texture. As natural marble resources are limited, artificial quartz slabs have emerged. Artificial quartz slabs are a new type of stone made of quartz sand as the main filler and unsaturated polyester resin as the adhesive, which is formed and cured by high pressure pressing.

[0003] However, since the better quality quartz sand is more used in photovoltaic and high purity sand, the quality of quartz sand for artificial boards is poor, which affects the quality of the quartz stone boards. In addition, the resin component is easily yellowed due to the influence of the environment during use, resulting in poor durability of the quartz stone boards. Summary of the invention

[0004] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a manufacturing process of a quartz stone plate with good permeability to produce a quartz stone plate with good permeability, good anti-permeability and good durability.

[0005] A process for producing a quartz stone plate with good permeability comprises the following steps:

[0006] S1 performs pickling treatment on quartz sand;

[0007] S2 The quartz sand after pickling is washed, neutralized and cleaned with an alkaline cleaning agent in sequence to obtain quartz sand without impurities and residual pickling solution;

[0008] S3: drying the quartz sand without impurities and residual pickling solution, and then ball milling to obtain quartz sand particles;

[0009] S4 performs an anti-oxidation modification treatment on the unsaturated polyester resin to obtain a modified unsaturated polyester resin;

[0010] S5: mixing and stirring the quartz sand particles, the modified unsaturated polyester resin, the white paste, the curing agent and the coupling agent to obtain a mixture;

[0011] S6: unloading the mixed material into a preset mold frame, flattening the material, covering it with paper, pressing it into shape, and then curing it to obtain a sheet material;

[0012] S7 grinds the plate material to obtain a quartz stone plate.

[0013] In one embodiment, quartz sand is obtained by crushing quartz stone; the method of pickling treatment is specifically performed as follows: immersing the quartz sand in a 0.1% oxalic acid solution for 20 to 30 minutes. In the present invention, the impurities such as iron, aluminum, titanium and chromium in the quartz sand are converted into soluble salts by reacting the oxalic acid solution with impurities such as iron, aluminum, titanium and chromium in the quartz sand.

[0014] Furthermore, the quartz sand after pickling is washed 2 to 3 times, and then an alkaline cleaning agent with a concentration of 0.1% is added, and after neutralization reaction in an ultrasonic oscillation environment for 15 to 20 minutes, the quartz sand is rinsed with clean water. In the present invention, the acid-base neutralization reaction is carried out by adding an alkaline cleaning agent to remove the acid wash solution remaining in the quartz sand. After pickling, the acid wash solution remaining in the quartz sand is completely removed by multiple cleanings and acid-base neutralization treatment in an ultrasonic oscillation environment, so as to avoid the acid wash solution affecting the curing effect of the resin component when the plate is formed.

[0015] In one embodiment, the drying process is carried out in a drying machine at a drying temperature of 60 to 80° C. for a drying time of 1 to 2 hours. In the present invention, the moisture content of the quartz sand is reduced by drying.

[0016] Furthermore, the ball milling shaping treatment is carried out in a ball mill, the ball milling speed is 500-1000r / min, and the ball milling time is 2-4h. The present invention shapes the quartz sand based on the ball milling treatment, thereby obtaining quartz sand particles with high sphericity, and the quartz sand particles are closely packed and the mortar body formed with the resin component has a dense structure and low porosity, thereby improving the anti-permeability and permeability of the obtained quartz stone plate.

[0017] In one embodiment, an antioxidant is added to perform an antioxidant modification treatment on the unsaturated polyester resin, and the specific operation is as follows: the antioxidant and the unsaturated polyester resin are stirred and mixed for 30 to 40 minutes at 60 to 80° C. to obtain a modified unsaturated polyester resin, and the amount of the antioxidant added is 0.5% to 1.5% of the polyester resin. The antioxidant is tert-butyl hydroquinone, dibutyl hydroxytoluene or thioglycolic acid. In the present invention, the antioxidant is added to inhibit the oxidation reaction, thereby avoiding the situation where the resin component is affected by oxygen and yellows.

[0018] In one embodiment, an oxidation stabilizer is used to perform an anti-oxidation modification treatment on an unsaturated polyester resin, and the specific operation is as follows: at 60-80°C, the oxidation stabilizer and the unsaturated polyester resin are stirred and mixed for 30-40 minutes to obtain a modified unsaturated polyester resin, and the amount of the oxidation stabilizer added is 0.5%-1% of the polyester resin. The oxidation stabilizer is a hindered amine light stabilizer, a UV absorber or a photodegradation inhibitor. In the present invention, an oxidation stabilizer is added to introduce an ultraviolet absorbing group, thereby overcoming the influence of ultraviolet rays on the resin components to maintain the stability of the color and performance of the quartz stone plate.

[0019] In one embodiment, the weight ratio of the quartz sand particles to the modified unsaturated polyester resin is 2 to 4:1, and the white paste, curing agent and coupling agent account for 4% to 7% of the mixture. The curing treatment is carried out in a curing furnace, the curing temperature is 75 to 85° C., and the curing time is 60 to 90 minutes.

[0020] A quartz stone plate is produced by the production process of the quartz stone plate with good permeability. The quartz stone plate is composed of the following parts by weight: 60-75 parts of quartz sand, 18-30 parts of modified unsaturated polyester resin, 0.5-1 part of white pulp, 2-4 parts of curing agent, and 1-2 parts of coupling agent.

[0021] In one embodiment, the curing agent is any one of vinyltriamine, diaminocyclohexane, methylenebiscyclohexylamine, ethylenediamine, diethylenetriamine and benzidine; the coupling agent is KH550, KH560, KH570, KH792, DL602 or DL171.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention converts impurities in quartz sand into soluble salts by pickling, thereby achieving the purpose of removing impurities and improving the purity of quartz sand, so that high-quality quartz stone plates with good whiteness and stable performance can be produced. At the same time, after pickling, the pickling liquid remaining in the quartz sand is completely removed by multiple washings and acid-base neutralization treatment under ultrasonic vibration environment, thereby overcoming the problem that the pickling liquid affects the curing effect of the resin component, resulting in poor quality of the obtained quartz stone plate.

[0024] The present invention shapes the quartz sand based on ball milling, thereby obtaining quartz sand particles with high sphericity, and the quartz sand particles are closely packed and the mortar body formed with the resin component has a dense structure and low porosity, thereby improving the anti-permeability and permeability of the obtained quartz stone plate. At the same time, the unsaturated polyester resin is subjected to antioxidant modification to avoid yellowing of the resin component, maintain the permeability of the quartz stone plate during use, and improve its durability in use. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. Additional aspects and advantages of the present invention will be given in part in the following description, and will become apparent from the following description, or will be understood through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.

[0026] As used herein, the terms "comprises," "including," "contains," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0027] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range limited by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including a range of "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When a numerical range is described in this article, unless otherwise specified, the range is intended to include its end values ​​and all integers and fractions within the range.

[0028] The specific embodiments of the present invention are described in detail below.

[0029] Example 1

[0030] This embodiment provides a process for manufacturing a quartz stone plate with good permeability, which includes the following steps:

[0031] S1 takes quartz stone and crushes it to obtain quartz sand, and then performs acid washing on the quartz sand, that is, immerses the quartz sand in 0.1% oxalic acid solution and reacts for 20 minutes.

[0032] S2 uses cleaning to wash the pickled quartz sand twice, then adds an alkaline cleaning agent with a concentration of 0.1%, and after neutralization reaction for 15 minutes under ultrasonic oscillation environment, rinses the quartz sand with clean water to obtain quartz sand without impurities and residual pickling solution.

[0033] S3: drying the quartz sand without impurities and residual pickling solution in a drying machine at a drying temperature of 60° C. for a drying time of 2 h, and then performing ball milling and shaping in a ball mill at a ball milling speed of 1000 r / min for a ball milling time of 2 h to obtain quartz sand particles;

[0034] S4: At 70°C, tert-butyl hydroquinone and unsaturated polyester resin were stirred and mixed for 35 minutes to obtain a modified unsaturated polyester resin, wherein the added amount of tert-butyl hydroquinone accounted for 1% of the polyester resin.

[0035] S5: Quartz sand particles, modified unsaturated polyester resin, white pulp, ethylene triamine and KH550 are mixed and stirred to obtain a mixture.

[0036] S6: unload the mixed material into a preset mold frame, flatten the material, cover it with paper, press it into shape, and then perform a curing treatment to obtain a sheet material. The curing treatment is performed in a curing furnace at a curing temperature of 80° C. and a curing time of 80 minutes.

[0037] S7 grinds the plate material to obtain a quartz stone plate material. The plate material is surface-shaped based on the grinding process, so that the obtained quartz stone plate material has a better glossiness.

[0038] The manufacturing process of this embodiment, the weight parts of the quartz stone plate produced are as follows: 60 parts of quartz sand, 18 parts of modified unsaturated polyester resin, 0.5 parts of white pulp, 2 parts of ethylenetriamine, and 1 part of KH550.

[0039] Example 2

[0040] This embodiment provides a process for manufacturing a quartz stone plate with good permeability, which includes the following steps:

[0041] S1 takes quartz stone and crushes it to obtain quartz sand, and then performs acid washing on the quartz sand, that is, immerses the quartz sand in 0.1% oxalic acid solution and reacts for 24 minutes.

[0042] S2 uses cleaning to wash the pickled quartz sand twice, then adds an alkaline cleaning agent with a concentration of 0.1%, and after neutralization reaction for 17 minutes under ultrasonic oscillation environment, rinses the quartz sand with clean water to obtain quartz sand without impurities and residual pickling solution.

[0043] S3: drying the quartz sand without impurities and residual pickling solution in a drying machine at a drying temperature of 70° C. for 1.5 h, and then performing ball milling and shaping in a ball mill at a ball milling speed of 500 r / min for 4 h to obtain quartz sand particles;

[0044] S4: At 60° C., butylated hydroxytoluene and unsaturated polyester resin were stirred and mixed for 40 minutes to obtain a modified unsaturated polyester resin, wherein the amount of butylated hydroxytoluene added accounted for 0.5% of the polyester resin.

[0045] S5: Quartz sand particles, modified unsaturated polyester resin, white pulp, diaminocyclohexane and KH560 are mixed and stirred to obtain a mixture.

[0046] S6: unload the mixed material into a preset mold frame, flatten the material, cover it with paper, press it into shape, and then perform a curing treatment to obtain a sheet material. The curing treatment is performed in a curing furnace at a curing temperature of 75° C. and a curing time of 90 minutes.

[0047] S7 grinds the plate material to obtain a quartz stone plate material. The plate material is surface-shaped based on the grinding process, so that the obtained quartz stone plate material has a better glossiness.

[0048] The quartz stone plate produced by the production process of this embodiment has the following composition by weight: 65 parts of quartz sand, 24 parts of modified unsaturated polyester resin, 0.5 parts of white pulp, 3 parts of diaminocyclohexane, and 1 part of KH560.

[0049] Example 3

[0050] This embodiment provides a process for manufacturing a quartz stone plate with good permeability, which includes the following steps:

[0051] S1 takes quartz stone and crushes it to obtain quartz sand, and then performs acid washing on the quartz sand, that is, immerses the quartz sand in 0.1% oxalic acid solution and reacts for 28 minutes.

[0052] S2 uses cleaning to wash the pickled quartz sand three times, then adds an alkaline cleaning agent with a concentration of 0.1%, and after neutralization reaction for 18 minutes under ultrasonic oscillation environment, rinses the quartz sand with clean water to obtain quartz sand without impurities and residual pickling solution.

[0053] S3: drying the quartz sand without impurities and residual pickling solution in a drying machine at a drying temperature of 75°C and a drying time of 2 hours, followed by ball milling and shaping in a ball mill at a ball mill speed of 800 r / min and a ball milling time of 3 hours to obtain quartz sand particles.

[0054] S4: At 77° C., the hindered amine light stabilizer and the unsaturated polyester resin were stirred and mixed for 30 minutes to obtain a modified unsaturated polyester resin, wherein the amount of the hindered amine light stabilizer added was 0.8% of the polyester resin.

[0055] S5: Quartz sand particles, modified unsaturated polyester resin, white pulp, methylenebiscyclohexylamine and KH570 are mixed and stirred to obtain a mixture.

[0056] S6: unload the mixed material into a preset mold frame, flatten the material, cover it with paper, press it into shape, and then perform a curing treatment to obtain a sheet material. The curing treatment is performed in a curing furnace at a curing temperature of 85° C. and a curing time of 65 minutes.

[0057] S7 grinds the plate material to obtain a quartz stone plate material. The plate material is surface-shaped based on the grinding process, so that the obtained quartz stone plate material has a better glossiness.

[0058] The manufacturing process of this embodiment is to manufacture a quartz stone plate whose weight parts are as follows: 70 parts of quartz sand, 26 parts of modified unsaturated polyester resin, 1 part of white pulp, 3.5 parts of methylenebiscyclohexylamine, and 1.5 parts of KH570.

[0059] Example 4

[0060] This embodiment provides a process for manufacturing a quartz stone plate with good permeability, which includes the following steps:

[0061] S1 takes quartz stone and crushes it to obtain quartz sand, and then performs acid washing on the quartz sand, that is, immerses the quartz sand in 0.1% oxalic acid solution and reacts for 30 minutes.

[0062] S2 uses cleaning to wash the pickled quartz sand three times, then adds an alkaline cleaning agent with a concentration of 0.1%, and after neutralization reaction for 20 minutes under ultrasonic oscillation environment, rinses the quartz sand with clean water to obtain quartz sand without impurities and residual pickling solution.

[0063] S3: drying the quartz sand without impurities and residual pickling solution in a drying machine at a drying temperature of 80°C and a drying time of 1 hour, followed by ball milling and shaping in a ball mill at a ball mill speed of 700 r / min and a ball milling time of 3.5 hours to obtain quartz sand particles.

[0064] S4: At 80°C, the UV absorber and the unsaturated polyester resin were stirred and mixed for 30 minutes to obtain a modified unsaturated polyester resin, and the amount of the oxidation stabilizer added accounted for 0.9% of the polyester resin.

[0065] S5: Quartz sand particles, modified unsaturated polyester resin, white pulp, diethylenetriamine and KH792 are mixed and stirred to obtain a mixture.

[0066] S6: unload the mixed material into a preset mold frame, flatten the material, cover it with paper, press it into shape, and then perform a curing treatment to obtain a sheet material. The curing treatment is performed in a curing furnace at a curing temperature of 77° C. and a curing time of 80 minutes.

[0067] S7 grinds the plate material to obtain a quartz stone plate material. The plate material is surface-shaped based on the grinding process, so that the obtained quartz stone plate material has a better glossiness.

[0068] The manufacturing process of this embodiment is to manufacture a quartz stone plate whose weight parts are as follows: 75 parts of quartz sand, 30 parts of modified unsaturated polyester resin, 1 part of white pulp, 4 parts of diethylenetriamine, and 22 parts of KH79.

[0069] The above embodiments are merely preferred implementations of the present invention. Any simple modification, amendment and substitution of the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.

Claims

1. A process for producing a quartz stone plate with good permeability, characterized in that: The following steps are involved: S1 performs pickling treatment on quartz sand; S2 The quartz sand after pickling is washed, neutralized and cleaned with an alkaline cleaning agent in sequence to obtain quartz sand without impurities and residual pickling solution; S3: drying the quartz sand without impurities and residual pickling solution, and then ball milling to obtain quartz sand particles; S4 performs an anti-oxidation modification treatment on the unsaturated polyester resin to obtain a modified unsaturated polyester resin; S5: mixing and stirring the quartz sand particles, the modified unsaturated polyester resin, the white paste, the curing agent and the coupling agent to obtain a mixture; S6: unloading the mixed material into a preset mold frame, flattening the material, covering it with paper, pressing it into shape, and then curing it to obtain a sheet material; S7 grinds the plate material to obtain a quartz stone plate.

2. The manufacturing process of the quartz stone plate with good permeability according to claim 1 is characterized in that: Taking quartz stone and crushing it to obtain the quartz sand; The specific operation of the pickling treatment method is as follows: immersing quartz sand in 0.1% oxalic acid solution and reacting for 20 to 30 minutes.

3. The manufacturing process of the quartz stone plate with good permeability according to claim 2 is characterized in that: Wash the acid-washed quartz sand 2 to 3 times with a cleaning agent, then add an alkaline cleaning agent with a concentration of 0.1%, neutralize the reaction under ultrasonic vibration for 15 to 20 minutes, and then rinse the quartz sand with clean water.

4. The manufacturing process of the quartz stone plate with good permeability according to claim 1 is characterized in that: The drying process is carried out in a drying machine at a drying temperature of 60 to 80° C. and a drying time of 1 to 2 hours.

5. The manufacturing process of the quartz stone plate with good permeability according to claim 4 is characterized in that: The ball milling shaping treatment is carried out in a ball mill, the ball milling speed is 500-1000 r / min, and the ball milling time is 2-4 hours.

6. The manufacturing process of the quartz stone plate with good permeability according to claim 1 is characterized in that: The antioxidant is added to perform antioxidant modification on the unsaturated polyester resin, and the specific operation is as follows: the antioxidant and the unsaturated polyester resin are stirred and mixed for 30 to 40 minutes at 60 to 80° C. to obtain a modified unsaturated polyester resin, and the amount of the antioxidant added accounts for 0.5% to 1.5% of the polyester resin; The antioxidant is tert-butylhydroquinone, butylated hydroxytoluene or thioglycolic acid.

7. The manufacturing process of the quartz stone plate with good permeability according to claim 1 is characterized in that: The oxidation stabilizer is used to perform an anti-oxidation modification treatment on the unsaturated polyester resin. The specific operation is as follows: the oxidation stabilizer and the unsaturated polyester resin are stirred and mixed for 30 to 40 minutes at 60 to 80° C. to obtain a modified unsaturated polyester resin, wherein the amount of the oxidation stabilizer added is 0.5% to 1% of the polyester resin; The oxidation stabilizer is a hindered amine light stabilizer, a UV absorber or a light degradation inhibitor.

8. The manufacturing process of the quartz stone plate with good permeability according to claim 1 is characterized in that: The weight ratio of the quartz sand particles to the modified unsaturated polyester resin is 2 to 4:1, and the white paste, curing agent and coupling agent account for 4% to 7% of the mixture; The curing treatment is carried out in a curing oven, the curing temperature is 75-85° C., and the curing time is 60-90 minutes.

9. A quartz stone plate, which is made by the manufacturing process of the quartz stone plate with good permeability as claimed in any one of claims 1 to 8, characterized in that: The quartz stone plate is composed of the following parts by weight: 60-75 parts of quartz sand, 18-30 parts of modified unsaturated polyester resin, 0.5-1 part of white paste, 2-4 parts of curing agent, and 1-2 parts of coupling agent.

10. The quartz stone plate according to claim 9, characterized in that: The curing agent is any one of vinyltriamine, diaminocyclohexane, methylenebiscyclohexaneamine, ethylenediamine, diethylenetriamine and benzidine; The coupling agent is KH550, KH560, KH570, KH792, DL602 or DL171.